2008
DOI: 10.1186/1471-2164-9-336
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction network of the Saccharomyces cerevisiae type 1 phosphatase Glc7

Abstract: BackgroundProtein kinases and phosphatases regulate protein phosphorylation, a critical means of modulating protein function, stability and localization. The identification of functional networks for protein phosphatases has been slow due to their redundant nature and the lack of large-scale analyses. We hypothesized that a genome-scale analysis of genetic interactions using the Synthetic Genetic Array could reveal protein phosphatase functional networks. We apply this approach to the conserved type 1 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…gac1 and bni4 were identified as hlc while reg1 as llc . Glc7p phosphatase interacts with different subunits each leading Glc7p to different substrates regulating several cellular processes as cell cycle, glycogen, sugar and lipid metabolism [60] , [61] . Gac1p and Bni4p recruit Glc7p phosphatase to glycogen synthase Gsy2p [62] or the bud neck [63] , respectively, and normally they may sequester some Glc7 phosphatase away from Snf1p.…”
Section: Discussionmentioning
confidence: 99%
“…gac1 and bni4 were identified as hlc while reg1 as llc . Glc7p phosphatase interacts with different subunits each leading Glc7p to different substrates regulating several cellular processes as cell cycle, glycogen, sugar and lipid metabolism [60] , [61] . Gac1p and Bni4p recruit Glc7p phosphatase to glycogen synthase Gsy2p [62] or the bud neck [63] , respectively, and normally they may sequester some Glc7 phosphatase away from Snf1p.…”
Section: Discussionmentioning
confidence: 99%
“…mitotic progression. We targeted the protein phosphatase Glc7p based on several observations: (1) genetic analysis has uncovered a functional interaction between Glc7p and Nup53p (Logan et al, 2008), a key component of the KTIP machinery; (2) Glc7p contains a putative Kap121p NLS and is concentrated in the nucleus of asynchronous cells; (3) Glc7p is an antagonist of Ipl1p function (reviewed in Lesage et al, 2011); and (4) mutations that reduce nuclear levels of Glc7p rescue growth of ipl1 ts mutants (Bharucha et al, 2008;Pinsky et al, 2006b;Tatchell et al, 2011). Using Glc7-GFP and cells containing the kap121-34 temperature-sensitive allele, we showed that nuclear accumulation of Glc7p was dependent on Kap121p ( Figure S6).…”
Section: Molecular Cellmentioning
confidence: 99%
“…The established lack of viability of glc7 -null cells [38] prompted us to take advantage of a catalytic mutant of the phosphatase ( glc7 - E101Q ), which displays defects in glucose metabolism but normal cell cycle progression and chromosome segregation [39]. The data showed that the pattern of Exo1 or Rad53 mobility during recovery from HU in the glc7 - E101Q background was not altered in comparison to control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%